Effects of dietary digestible lysine levels on protein and fat deposition in the carcass of broilers - Tavernari,F de C (2009)
An experiment was carried out to evaluate the effects of different levels of digestible lysine in the diets of male and female broilers on protein and fat deposition. A total of 2160 Avian Farms broilers. A completely randomized experimental design was applied, and treatments consisted of the effects of three digestible lysine levels nested within each sex, with 12 replicates and 30 birds per experimental unit. The adopted digestible lysine levels corresponded to 92.5, 100.0, and 107.5% of the nutritional requirements of phases 1 to 21 days, 22 to 42 days, and 43 to 56 days of age, respectively. In each phase, the experimental diets contained similar calorie and protein levels within each sex. No significant effects of lysine levels were found on dry matter and fat percentages in the carcass of birds during the evaluated periods. Also, there were no significant effects of lysine levels on protein and fat deposition in males or females. However, males presented higher protein deposition and lower fat deposition than females during the total experimental period. Gompertz equations showed that females deposit more fat and less protein than males, and that this affected the fall in the curve of protein deposition, when the curve of fat deposition was still rising. Therefore, it was concluded that the older the broilers at slaughter, the higher their body fat content and the lower their body protein content, particularly in females.